Case report: High-grade hidradenocarcinoma of the chest wall with insights from 18F-FDG PET/CT imaging and a review of the literature - Li, Wenxin; Hu, Xianwen; Tan, Na; Wang, Pan (Frontiers in Oncology, 2024)
Hidradenocarcinoma (HAC) is a rare neoplasm that typically occurs in the head and neck region but seldom affects the chest wall. Histopathology and immunohistochemistry remain essential for diagnosing HAC, although their clinical utility in determining metastasis can be limited. Given the pathological rarity and histopathological heterogeneity of HAC, we report a case demonstrating the utility of positron emission tomography/computed tomography (PET/CT) combined with immunohistochemical examination for the accurate diagnosis and staging of HAC. An 84-year-old woman presented to our hospital with a right chest wall and axillary mass. A pathological examination was performed, which revealed a malignancy of epithelial origin. The immunohistochemical examination confirmed a high-grade hidradenocarcinoma. Subsequently, PET/CT examination showed significant hypermetabolism in the right chest wall and its ipsilateral axillary and subclavian lymph nodes. Combined with pathological findings, these results confirmed metastatic hidradenocarcinoma, leading to a TNM classification of T2N3M (stage IV). A literature review revealed that HAC rarely occurs in the chest wall but tends to metastasize. However, the prognosis is favorable, especially with early diagnosis and surgical intervention. 18F-FDG PET/CT examination is a valuable staging tool in the comprehensive assessment of systemic tumor metastasis. Combining PET/CT with pathological examination enhances diagnostic and staging accuracy, enabling timely treatment and improving outcomes.